(untitled) (Research, Society and Development, 2022)
Objective: To identify the perception of lay people in relation to the care of cardiorespiratory arrest in a pre-hospital setting (PHC). Methodology: This is an Integrative Review, carried out between February and April 2022, the time frame established for the research were selected and published scientific articles from 2008 to April 2022, in the languages in Portuguese, English and Spanish in the aforementioned Scientific Electronic Library (SciELO) databases and in Latin American and Caribbean Literature on Health Sciences (LILACS), through the Virtual Health Library (VHL). The key words were established according to the Descriptors in Health Sciences (DeCS). Result: the number of articles selected were 132 and after the inclusion/exclusion criteria made up the amount of 04 eligible articles. Final considerations: Through the research, it is concluded that so far, in the State of São Paulo, there are no records of training aimed at the implementation of first aid in schools as a permanent solution to the problem presented. It is of fundamental importance to implement the draft laws in order to reduce mortality by stop in the midst of society, through social projects, which culminate in prevention, promotion and guidance actions as preventive measures and actions to be implemented in practice.